Comparative study of USLE and RUSLE model in predicting soil erosion events using GIS in Penang Island - Nur Zulaikha Hamizul; Haris Abdul Rahim; Nor Aizam Adnan; Raiz Razali; Mohd Shahmy Mohd Said; Fazly Amri Mohd (Penerbit Universiti Kebangsaan Malaysia, 2025)
Around the world, soil erosion is a major environmental concern, especially in tropical areas like Malaysia's Penang Island. In order to assess the accuracy and dependability of both models in estimating soil erosion risk, this study will use the USLE and RUSLE models to estimate soil erosion on Penang Island. Additionally, the predictions generated by the RUSLE model will be compared with site verification. Important parameters were extracted from spatial datasets and added to the models, including the rainfall erosivity factor, soil erodibility factor, slope length and steepness factor, vegetation management factor, and supporting conservation practices factor. In order to analyse and map the risk of soil erosion throughout Penang Island, the research integrated GIS technology with both the USLE and RUSLE models. The findings suggest that the RUSLE model outperforms the USLE model in detecting regions vulnerable to soil erosion. Thus, the RUSLE model demonstrates more reliable data and typically aligns well with real site verification outcomes. In general, the forecast of soil erosion through RUSLE can be effectively contrasted with the USLE model within GIS. This study's recommendation suggests gathering data for model inputs to enhance the precision of soil erosion forecasts on Penang Island.